Relevance of rock engineering to civil engineers! - Dr. Rock, . (Faculty of Civil Engineering & Earth Resources, 2018)
The factors that are important when considering erection of structures on rock foundations are faults, joints, stratigraphy or potential cavities due to karstic features in limestone formation. The rockstructure is an important consideration in geotechnical design. For example, rapid weathering of rock is a vital factor on rock slope stability design.